Clustering Women Violence Cases Based on Number in Central Java Province Using K-Means Algorithm - Tantisnio, Fanika Putri; Wakhidah, Nur (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
Cases of violence against women are one of the cases that require special attention, especially in the Central Java Province area. This study aims to classify the number of cases of violence against women (age 18+) based on data from 2022 and 2023 using the K-Means algorithm. Through the K-Means método, the regions are classified into 2 clusters based on the pattern of the number of cases in the 2 years. The results of clustering show two main groups: the first cluster which is from the majority of regions with a fairly low number of violent cases, and the second cluster which includes Semarang City as a very high number of violent cases. This study provides an overview of cases of violence against women in Central Java Province and identifies areas with higher case rates. This research is expected to be used as a basis for more appropriate policy-making to reduce the rate of violence against women in the most affected areas.